Infeksi Cacing Nematoda Usus Pada Anak Kelas 1 dan 2 Sekolah Dasar - Oki Irawati; Sartini Sartini; Ida Fauziah (Universitas Medan Area, 2021)
Worm disease is still one of the health problems in Indonesia. Personal hygiene such as playing in the school ditch, on the ground, playing dirty and some children do not use footwear, long nails and the habit of not washing their hands with soap before and after playing, thereby increasing the risk of intestinal worms in children. This study aims to determine the percentage and types of intestinal nematode worm eggs that infect elementary school children grades 1 and 2 Raudathul Jannah Foundation, Penraujan Private Elementary School, Sunggal District, Deli Serdang Regency. The method used in this study was direct stool examination. Based on the results of the examination of 48 samples of elementary school students in grades 1 and 2, it was found that 3 samples were positively infected with intestinal nematode worm eggs with a percentage of 6.25% and there were 2 types of worm eggs that infect, namely Ascaris lumbricoides and Trichuris trichiura. Where sample (S 12) was infected with Trichuris trichiura worm eggs, sample (S 37) was infected with Ascaris lumbricoides worm eggs and sample (S 46) was infected with both types of worm eggs, namely Ascaris lumbricoides and Trichuris trichiura.